BIMBINGAN KONSELING HOLISTIK UNTUK MEMBANTU PENYESUAIN DIRI MUALAF TIONGHOA MESJID MUHAMMAD CHENGHO PALEMBANG - Neni Noviza (Wardah, 2013)
This study aims to determine how the adjustment itself on converts . Subjects were converts tionghoa mosque Muhammad Chengho Palembang. This study is a qualitative study with a phenomenological approach . Data were obtained and collected through semi-structured interviews and observations by using the interview guide and checklist list . Then , the data were analyzed using analysis of data reduction , display / presentation of data and making conclusions / verification of interactive models of Miles & Huberman ( 1992 ) . The results showed that the problems experienced by the Muslim convert Muhammad Cheng Ho Mosque is a matter of family , career and employment issues , and marginalized by other communities. The Individuals who have a religious conversion " more tasks " that adjust from changes in themselves and habits to obtain satisfactory relationships with other people and our environment . The problems associated with the present most fundamental change in the lives of converts after deciding to perform religious conversion requires the adjustment mainly in the habit of worship and in the family who did not convert to the faith of the subject . Holistic counseling through religious counseling and bibliotherapy approach is one way to help the adjustment to convert